Pemasaran Produk dengan Pendekatan AIDA oleh Influencer di Media Sosial TikTok - Tjoa, Hans Benedict; Sutjipto, Catherine Christabel; Valerie, Valencia; Wijayanti, Sri Hapsari (Jurnal Riset Komunikasi (JURKOM), 2024)
Nowadays, social media is widely used by marketers, including influencers, to promote products or services. One promotional technique used as a reference for preparing content on social media is the AIDA approach. AIDA is an effective marketing stage, starting from captivating the audience (attention), growing interest (interest), arousing desire (desire), and motivating audience action (action). The purpose of this study is to describe the AIDA approach used by NS as influencer on TikTok when marketing household appliances. This research is qualitatively descriptive, using observation techniques of video shows and content analysis of the three videos belonging to NS. The three videos were aired in 2023 and randomly selected as the object of research. Content analysis is guided by the stages contained in AIDA, namely attention, interest, desire, and action. This study found that the AIDA approach in marketing on TikTok can help influencers lead their audience from curiosity, interest, to thinking to action. Marketing carried out using TikTok is classified as softsale because it is simpler and more effective to implement.